2017
DOI: 10.13189/ujer.2017.050513
|View full text |Cite
|
Sign up to set email alerts
|

Correlation and Predictive Relationship between Self-determination Instruction and Academic Performance of Students with Disabilities

Abstract: The purpose of this study was to investigate the correlation and probable predictive relationship between self-determination skills taught by special education teachers and the academic performance of students with disabilities from junior high schools in Taiwan. The subjects included teachers from resource rooms and self-contained classrooms (n = 106) and students with disabilities in these classes (n = 106). Two measures, the Teaching Self-determination Scale (TSDS) and the Basic Learning Competency Assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
(28 reference statements)
1
2
0
Order By: Relevance
“…The findings were consistent with the results of previous research which showed that self-determination skills education can lead to increased scholastic performance and achievement of educational goals in youth with disabilities ( 15 - 18 ). In general, it seems self-determination education is effective on the scholastic achievement of the youth at risk of emotional-behavioral disorders like those with disabilities.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings were consistent with the results of previous research which showed that self-determination skills education can lead to increased scholastic performance and achievement of educational goals in youth with disabilities ( 15 - 18 ). In general, it seems self-determination education is effective on the scholastic achievement of the youth at risk of emotional-behavioral disorders like those with disabilities.…”
Section: Discussionsupporting
confidence: 92%
“…Interventions based on "Peer-Mediated Instruction (PMI)" are additionally a method as an evidence-based exercise to improve the educational outcomes of students with emotional-behavioral disorders addressed in the studies ( 8 ). Also, within the last 20 years, many studies have reviewed the effects of self-determination education among students with disabilities and self-determination has been realized and recognized as one of the most important factors in the successful transfer of students from education to independence ( 6 , 15 - 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is a correlation between self-determination skills and the academic performance of SWDs. Those with the skills of independence, psychological empowerment, and self-realization have been shown to achieve higher academic outcomes [10].…”
Section: Self-determination Theory (Sdt)mentioning
confidence: 99%